2011
DOI: 10.1007/s00484-011-0434-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatial structure of the abiotic environment and its association with sapling community structure and dynamics in a cloud forest

Abstract: Analyzing the relationship between the spatial structures of environmental variables and of the associated seedling and sapling communities is crucial to understanding the regeneration processes in forest communities. The degree of spatial structuring (i.e., spatial autocorrelation) of environmental and sapling community variables in the cloud forest of Teipan, S Mexico, were analyzed at a 1-ha scale using geostatistical analysis; after fitting semivariogram models for each set of variables, the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 77 publications
0
6
1
Order By: Relevance
“…It is well known that light is a crucial factor in sapling establishment, and its importance has been observed in previous studies conducted in tropical wet forests (Montgomery & Chazdon ), as well as in cloud forests (Mejía‐Domínguez et al. ). However, our results revealed that the level of light required for sapling establishment in the studied cloud forest differs from those reported for tropical rain forests, as also distances of density dependence differed.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…It is well known that light is a crucial factor in sapling establishment, and its importance has been observed in previous studies conducted in tropical wet forests (Montgomery & Chazdon ), as well as in cloud forests (Mejía‐Domínguez et al. ). However, our results revealed that the level of light required for sapling establishment in the studied cloud forest differs from those reported for tropical rain forests, as also distances of density dependence differed.…”
Section: Discussionmentioning
confidence: 83%
“…Consequently, the spatial distribution of adult trees influences the spatial distribution of saplings in cloud forests, as elsewhere (Mejía‐Domínguez et al. ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These heterogeneous environmental factors can play an important role in the growth and regeneration of plants in different patch types with different ecological characteristics. Heterogeneous patches show selectivity for species of a diversity sizes and functions ( Mejía-Domínguez, Meave & Díaz-Ávalos, 2012 ). Our present results support and enrich those of previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…For various gap-forming processes, canopy dynamics are diverse and patches change with time and space. Diverse patches present heterogeneous environmental factors providing the necessary ecological basis for the coexistence of species (or functional groups) with different ecological demands in their different life history stages ( Mejía-Domínguez, Meave & Díaz-Ávalos, 2012 ). Mosaic patches can further be subdivided: gap and non-gap ( Brokaw, 1982 ); gap, non-gap and expanding gap; gap, closed canopy and gap adjacent areas ( Manabe & Yamamoto, 1997 ); and closed canopy type (CC-Type), gradually closing type (GC-Type), expanding gap (GG-Type) and newly created gap type (NG-Type) ( Manabe et al, 2009 ).…”
Section: Introductionmentioning
confidence: 99%